2011
DOI: 10.1007/s11738-011-0769-x
|View full text |Cite
|
Sign up to set email alerts
|

Case study of a biological control: Geobacillus caldoxylosilyticus (IRD) contributes to alleviate salt stress in maize (Zea mays L.) plants

Abstract: The inevitable exposure of crop plants to salt stress is a major environmental problem emerged from the presence of excess NaCl radicals in the soil. Handling the problem in maize plants using a biological agent was the main interest of the present study. The non-pathogenic, halophytic, facultative aerobic bacterium Geobacillus caldoxylosilyticus IRD that was isolated from Marakopara pond in the Atoll Tikehau (French Polynesian, 2005) and found tolerant to salt stress until 3.5% NaCl (w/v). An artificial symb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…However, one study demonstrates the use of G. thermoglucosidasius strain PMB207 as a biocontrol agent in the commercial production of lily bulbs, with the capacity to be used alone or in combination with the fungicide Sporgon at low concentration (<100 mg/mL) (Chung, Wu, Hsu, Huang, & Huang, 2011). Another study demonstrated the potential use of G. caldoxylosilyticus IRD in controlling or protecting maize plants against high salt stress (Abdelkader & Esawy, 2011). The field of biocontrol is currently still in its infancy, but may be exploitable for commercial use once regulatory hurdles imposed by the International Organization for Biological Control and REBECA (Regulation of Biological Control) are overcome (Bale, Van Lenteren, & Bigler, 2008).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…However, one study demonstrates the use of G. thermoglucosidasius strain PMB207 as a biocontrol agent in the commercial production of lily bulbs, with the capacity to be used alone or in combination with the fungicide Sporgon at low concentration (<100 mg/mL) (Chung, Wu, Hsu, Huang, & Huang, 2011). Another study demonstrated the potential use of G. caldoxylosilyticus IRD in controlling or protecting maize plants against high salt stress (Abdelkader & Esawy, 2011). The field of biocontrol is currently still in its infancy, but may be exploitable for commercial use once regulatory hurdles imposed by the International Organization for Biological Control and REBECA (Regulation of Biological Control) are overcome (Bale, Van Lenteren, & Bigler, 2008).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Azotobacter chroococcum improved nutrition [108], Geobacillus sp. increased photosynthetic rate [111], and Rhizobium spp., Rhizobium tropici strain CIAT, A. brasilense strains Ab-V5 and Ab-V6 [107], and A. faecalis [101] enhanced chlorophyll content and photosynthetic rate by increased accumulation of proline and osmotic adjustments in maize plants.…”
Section: Osmotic Adjustmentmentioning
confidence: 96%
“…Parageobacillus caldoxylosilyticus was first isolated and identified as Saccharococcus caldoxylosilyticus from local soil in Melbourne, Australia (Ahmad et al, 2000), before it was classified as Geobacillus caldoxylosilyticus in 2001 (Fortina et al, 2001) and lastly classified as Parageobacillus caldoxylosilyticus in 2016 (Aliyu et al, 2016). This species was found not only in soil (Ahmad et al, 2000), chipped woody waste (Yunitsyna et al, 2019), oilcontaminated soil (Adlan et al, 2020, volcanic soil (Seo et al, 2011), but it was also found in a liquid such as seawater (Adlan et al, 2020), pond water (Abdelkader & Esawy, 2011), hot spring (Ibrahim & Ahmad, 2017Kolcuoğlu et al, 2010), central heating system water (Obojska et al, 2002), and in the dairy product (Berendsen et al, 2016). Besides, the species also showed high adaptability towards various environmental stress other than temperature, as it was able to tolerate glyphosate, heavy metal toxicity, oil contamination, as well as high salinity and alkalinity (Obojska et al, 2002;Abdelkader & Esawy, 2011;Ibrahim & Ahmad, 2017;Yunitsyna et al, 2019;Adlan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This species was found not only in soil (Ahmad et al, 2000), chipped woody waste (Yunitsyna et al, 2019), oilcontaminated soil (Adlan et al, 2020, volcanic soil (Seo et al, 2011), but it was also found in a liquid such as seawater (Adlan et al, 2020), pond water (Abdelkader & Esawy, 2011), hot spring (Ibrahim & Ahmad, 2017Kolcuoğlu et al, 2010), central heating system water (Obojska et al, 2002), and in the dairy product (Berendsen et al, 2016). Besides, the species also showed high adaptability towards various environmental stress other than temperature, as it was able to tolerate glyphosate, heavy metal toxicity, oil contamination, as well as high salinity and alkalinity (Obojska et al, 2002;Abdelkader & Esawy, 2011;Ibrahim & Ahmad, 2017;Yunitsyna et al, 2019;Adlan et al, 2020). These unique properties of P. caldoxylosilyticus made this species a promising candidate for the production of industrially applicable thermostable enzymes such as xylanase, maltogenic amylase, and acylhomoserine lactonase, at the same time, offer an environmentally friendly solution of herbicide degradation, bioremediation of harmful chromium IV oxide, and crude oil paraffin wax degradation (Obojska et al, 2002;Kolcuoğlu et al, 2010;Abdelkader & Esawy, 2011;Seo et al, 2011;Rahim & Ahmad, 2016;Ibrahim & Ahmad, 2017;Yunitsyna et al, 2019;Adlan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation